Understanding the Role of Public Administration in Implementing Action on the Social Determinants of Health and Health Inequities - Gemma Carey; Sharon Friel (Kerman University of Medical Sciences, 2015)
Many of the societal level factors that affect health - the 'social determinants of health (SDH)' - exist outside the health sector, across diverse portfolios of government, and other major institutions including non-governmental organisations (NGOs) and the private sector. This has created growing interest in how to create and implement public policies which will drive better and fairer health outcomes. While designing policies that can improve the SDH is critical, so too is ensuring they are appropriately administered and implemented. In this paper, we draw attention to an important area for future public health consideration - how policies are managed and implemented through complex administrative layers of 'the state.' Implementation gaps have long been a concern of public administration scholarship. To precipitate further work in this area, in this paper, we provide an overview of the scholarly field of public administration and highlight its role in helping to understand better the challenges and opportunities for implementing policies and programs to improve health equity.